PENGARUH PERJANJIAN COMPREHENSIVE ECONOMIC AND TRADE AGREEMENT (CETA) OLEH UNI EROPA DAN KANADA TERHADAP EKONOMI POLITIK INTERNAL NEGARA EROPA - Khusaidah, Nisa'atin (Global and Policy Journal of International Relations, 2018)
ABSTRACTCETA has a great influence in the economic progress of European countries, especially in the free trade flow between countries in the world. The removal of large-scale barriers between the EU and Canada has become an important point in this agreement. On the other hand, the CETA is considered a challenge in the politics of European countries because in reality not all European societies give full support to CETA because it is perceived to only provide the economic decline of European countries and is considered to be only going into the same hole, given the Union Europe, which has also had economic cooperation with other countries and not produce results. The EU is perceived as too closed in every process of agreement making and even less involving the aspirations of other European societies.Keywords: EU, Canada, Donald Trump, CETA, Economy PoliticsDOI: https://doi.org/10.33005/jgp.v6i01.1881